A moving blocker system for cone‐beam computed tomography scatter correction. Issue 7 (18th June 2013) - Ouyang, Luo; Song, Kwang; Wang, Jing
Abstract : Purpose: : Scatter contamination in cone‐beam computed tomography (CBCT) degrades the image quality by introducing shading artifacts. A moving‐blocker‐based approach has been proposed to simultaneously estimate scatter and reconstruct the complete volume within field of view (FOV) from a single CBCT scan. Promising results were obtained from our simulation studies. In this work, the authors demonstrated experimentally the effectiveness of the moving‐blocker‐based scatter correction approach by implementing a moving blocker system on a LINAC on‐board kV CBCT imaging system. Methods: : A physical attenuator (i.e., "blocker") consisting of equal spaced lead strips was mounted on a linear actuator. A step motor connected to the actuator drove the blocker to move back and forth along gantry rotation axis during the CBCT acquisition. Scatter signal was estimated from the blocked region of imaging panel, and interpolated into the unblocked region. A statistics‐based iterative image reconstruction algorithm was used to reconstruct CBCT images from unblocked projections after the scatter signal was subtracted. Experimental studies were performed on a Catphan phantom and an anthropomorphic pelvis phantom to evaluate performance of the moving blocker system. Results: : The scatter‐induced shading artifacts were substantially reduced in the images acquired with the moving blocker system. CT number error in selected regions of interest reduced from 318 to 17 and from 239 to 10 for the Catphan phantom and pelvis phantom, respectively. Conclusions: : The authors demonstrated experimentally that the moving blocker system can successfully estimate the scatter signal in projection data and obtain complete volumetric information within the FOV using a single scan.